Medicalization under prohibition: the tactics and limits of medicalization in the spaces where people use illicit drugs. (4th March 2021) - Kolla, Gillian; Strike, Carol
Abstract: The 'Satellite Sites' are a harm reduction intervention in which people who use illicit drugs are employed by a community health centre to run satellite harm reduction programs within their homes. Satellite Sites straddle two worlds, at once sites of illicit and stigmatized activities, while also being sites of public health intervention. They offer a unique opportunity to examine the challenges of medicalizing a place that is still criminalized. Using data collected during 7 months of ethnographic observation and 20 interviews with key members of the program, we explore the tactics of medicalization that are deployed to legitimize the Satellite Sites. Medicalization provides legitimacy to Satellite Sites, and provides people who use drugs who run the Satellite Sites with some protection from the criminal justice system. Our results explore the friction between processes of medicalization and criminalization, with continued criminalization of drug possession and distribution negatively impacting the uptake and effectiveness of public health recommendations. Study findings highlight how the ability of public health authorities to develop safer environment interventions to improve the health of people who use drugs—including measures to address the current overdose crisis - may be severely limited by the continued criminalization of drug use.